2004
DOI: 10.1002/iroh.200310661
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Size Spectra and Plankton Diversity in a Shallow Eutrophic Lake

Abstract: Biomass size spectra collate structural and functional attributes of plankton communities enabling standardised temporal and cross-system comparisons and may be rapidly obtained by automated particle counters. To examine how differences in plankton communities from highly eutrophic and more oligotrophic lakes are reflected in size spectra, a three-year time series of biomass size spectra was established for polymictic, eutrophic Lake Müggelsee, based on approximately weekly sampling and microscopic enumeration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 46 publications
1
28
2
3
Order By: Relevance
“…In addition, the abundance of ciliate was significantly correlated with TN concentration at Lake Center in this study (r = 0.62, P = 0.032). Many other studies have demonstrated that the composition of microbial eukaryotic communities is related to trophic status (Gaedke et al 2004;Lefranc et al 2005;Lepère et al 2006;Moore et al 2008). For example, Lepère et al (2006) found that nutrients, especially nitrogenous nutrients and total phosphorus, play a significant role in structuring small eukaryotic communities.…”
Section: Seasonal Variations and Regulation Of The Meccmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, the abundance of ciliate was significantly correlated with TN concentration at Lake Center in this study (r = 0.62, P = 0.032). Many other studies have demonstrated that the composition of microbial eukaryotic communities is related to trophic status (Gaedke et al 2004;Lefranc et al 2005;Lepère et al 2006;Moore et al 2008). For example, Lepère et al (2006) found that nutrients, especially nitrogenous nutrients and total phosphorus, play a significant role in structuring small eukaryotic communities.…”
Section: Seasonal Variations and Regulation Of The Meccmentioning
confidence: 96%
“…The result suggests that cladocera and copepoda may exert differential top-down regulation of microbial eukaryotes in the microbial food web (Lepère et al 2006). The preferred food size for the filtering cladocera is less than 40-50 lm; therefore, they could exert a pronounced effect on the whole protist community (Auer and Arndt 2001;Gaedke et al 2004;Jürgens and Stolpe 1995). Copepoda select a larger particle size than cladocera and are known to be efficient selective grazers of larger Aquat Ecol (2010) 44:1-12 9 planktonic ciliates (Auer and Arndt 2001;Sommer et al 2003;Zöllner et al 2003) and are probably of minor importance as grazers of nanoplankton (Jür-gens and Stolpe 1995).…”
Section: Seasonal Variations and Regulation Of The Meccmentioning
confidence: 98%
“…Additionally, there should be a higher vulnerability of heterotrophic nanoplank- ters to high daphnids abundance than that of the equally sized autotrophs. A precondition for both circumstances is a high abundance of large daphnids (Tittel et al 1998;Gaedke et al 2004). However, in Lake Kastoria, the overall size composition of zooplankton was dominated by sizes up to 300 m (Fig.…”
Section: Periodsmentioning
confidence: 99%
“…There is relatively little information available on how species richness influences fish community size distributions, particularly in small lakes (Duplisea 2000;Gaedke et al 2004;Sprules 2008). It is possible that even single species lakes show a predicable size structure as long as there is competition for limited food resources and size-based predation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that species diversity has little effect on size spectra slope in large systems, or beyond some yet undetermined number of species. Similarly, Gaedke et al (2004) found that diversity of plankton had little effect on the shape of size spectra in a large (730 ha), shallow eutrophic lake. Contrary to the aforementioned studies, Duplisea (2000) suggested that size spectra of the Baltic Sea benthos may be altered when one or two ecologically important species are reduced in abundance; these results suggest that as species richness decreases the likelihood of single (ecologically important) species population dynamics having a strong influence on CSS increases, as will the variability in size structure (i.e., tend toward stochastic structure).…”
Section: Discussionmentioning
confidence: 99%